Subfertility Caused by Altered Follicular Development and Oocyte Growth in Female Mice Lacking PKBalpha/Akt1(1) - Brown, Caitlin (Biol Reprod, 2010)
Mammalian females are endowed with a finite number of primordial follicles at birth. Immediately following formation of the primordial follicle pool, cohorts of follicles are either culled from the ovary or are recruited to grow until the primordial follicle population is depleted. The majority of ovarian follicles, including the oocytes, undergo atresia through apoptotic cell death. As PKBalpha/Akt1 is known to regulate apoptosis, we asked whether Akt1 functioned in the regulation of folliculogenesis in the ovary. Akt1(−/−) females display reduced fertility and abnormal estrous cyclicity. At Postnatal Day (PND) 25, Akt1(−/−) ovaries possessed a reduced number of growing antral follicles, significantly larger primary and secondary oocytes, and an increase in the number of degenerate oocytes. By PND90, there was a significant decrease in the number of primordial follicles in Akt1(−/−) ovaries relative to Akt1(+/+). In vivo granulosa cell proliferation was reduced, as were expression levels of Kitl and Bcl2l1, two factors associated with granulosa cell proliferation/survival. No compensation was observed by Akt2 or Akt3 at the mRNA/protein level. Significantly higher serum LH and trends for lower FSH and higher inhibin A and lower inhibin B relative to Akt1(+/+) females were observed in Akt1(−/−) females. Exposure to exogenous gonadotropins resulted in an increase in the number of secondary follicles in Akt1(−/−) ovaries, but few mature follicles. Collectively, our results suggest that PKBalpha/Akt1 plays an instrumental role in the regulation of the growth and maturation of the ovary, and that the loss of PKBalpha/Akt1 results in premature ovarian failure.